THE EFFECT OF ORGANIZATIONAL CULTURE, WORK ETHIC, KNOWLEDGE LEVEL OF ACCOUNTING, AND MORAL HAZARD ON THE QUALITY OF COMPANY’S FINANCIAL REPORT INFORMATION (The study is accounting and finance employees in the whole national private company in Gresik) - Yanuar Lazuardi; Abid Muhtarom (Akuisisi: Jurnal Akuntansi, 2017)
This research was conducted to test the effect of independent variables, they are organizational culture, work ethic, level knowledge of accounting and accountant’s moral hazard on the dependent variable, that is the quality of company's financial report information, either simultaneously or partially. The type of this research is causal associative with quantitative approach, the research aims to determine the effect of two or more variables, with the approach of testing the theory by measuring the variables with numbers and analyze the data with statistical procedures. The population of this study is the accounting and finance employees in the whole national private company in Gresik. Sampling was done by nonprobability sampling method with judgement sampling approach, the results of selected judgement sample is the accounting and finance employees in 13 companies. The data source used is primary data derived from the answers of respondents in the research questionnaire. The data are processed with SPSS 16.0 for Windows with multiple linear regression test. The results of this research show that: 1) Simultaneously, the variable of organizational culture, work ethic, knowledge level of accounting and accountant’s moral hazard affect the quality of company's financial report information. 2) Partially from four independent variables, the variable of organizational culture does not have a strong influence on the dependent variable quality of the company's financial report information.